2018
DOI: 10.1021/acs.energyfuels.8b02205
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Roles of Absorber and Desorber Catalysts in the Heat Duty and Heat of CO2 Desorption from Butylethanolamine–2-Amino-2-methyl-1-propanol and Monoethanolamine–Methyldiethanolamine Solvent Blends in a Bench-Scale CO2 Capture Pilot Plant

Abstract: The performance of a novel bi-blend butylethanolamine (BEA)–2-amino-2-methyl-1-propanol (AMP) solvent developed from an earlier work using a semi-batch method was validated in a bench-scale CO2 capture pilot plant in terms of its CO2 capture performance criteria compared to the benchmark 7 M monoethanolamine (MEA)–methyldiethanolamine (MDEA) solvent blend. Also, the synergistic benefits provided by placement of a solid acid catalyst (HZSM-5) in the desorber column and a solid base catalyst (K/MgO) used for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 38 publications
0
46
0
Order By: Relevance
“…The cyclic capacity for MEA + AMP/MEA + BEA solvents at different concentrations was listed in Equation . The α rich was α eq of amine blends, and α lean was 0.30 mol/mol for bench‐scale process of BEA + AMP 7,8 Desorption parameter=Initial desorption rate×cyclic capacityheat duty Iitalicdes¯italicrate=normald0.25emnCO2dt=CVdαnormalV0.25emdt=Cdt.7em()mol0.35emCO2/normalL.0.35emmin Cyclic capacity=()αrichαleannormalC×normalV0.25em()mol0.25emCO2/normalL …”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…The cyclic capacity for MEA + AMP/MEA + BEA solvents at different concentrations was listed in Equation . The α rich was α eq of amine blends, and α lean was 0.30 mol/mol for bench‐scale process of BEA + AMP 7,8 Desorption parameter=Initial desorption rate×cyclic capacityheat duty Iitalicdes¯italicrate=normald0.25emnCO2dt=CVdαnormalV0.25emdt=Cdt.7em()mol0.35emCO2/normalL.0.35emmin Cyclic capacity=()αrichαleannormalC×normalV0.25em()mol0.25emCO2/normalL …”
Section: Theorymentioning
confidence: 99%
“…The most commonly used energy‐efficient approach is by either solvent improvement, optimization of process intensification, or improvement of packing performance 1,6 . Particularly, adoption and development of improved solvents 7 into a good‐performance structured packing column 8 is a very promising method to reduce heat duty and operation costs 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, based on recent studies, the effects of solid base chemicals to MEA (K/MgO, CaCO 3 and MgCO 3 ) [18,19] and DEA (CaCO 3 and MgCO 3 ) [20] on CO 2 absorption have been verified. They accelerate the CO 2 absorption rates.…”
Section: Introductionmentioning
confidence: 99%
“…The characterization results indicated that catalytic activity was affected by specific surface area, acid strength, and the quantity of acid sites on the acidic catalysts. Raphael et al reported that desorption energy consumption could be reduced by 42% with HZSM‐5 catalyst in a full cyclic system . The catalytic desorption kinetics of MEA and MDEA‐MEA with catalysts (HZSM‐5 and γ ‐Al 2 O 3 ) were studied and it was concluded that HZSM‐5 showed faster kinetic and lower activation energy than γ ‐Al 2 O 3 at CO 2 loading range from 0.28 to 0.50normalmolCO2/normalmolnormalMEA …”
Section: Introductionmentioning
confidence: 99%